Detection of Hand Position using 3-D Computer Vision - Serafinavičius, P.; Daunys, G. (Elektronika ir Elektrotechnika, 2006)
Determination of hand position based on one of the simplest technique of 3-D points reconstruction – pinhole camera model and triangulation – is described. Evaluation of this method was carried out using specially developed software based on open source OpenCV library. The software measures an angle between different arm directions in real time. The results of experimental evaluation prove that the highest accuracy is achieved when a plane of measuring angle is perpendicular to cameras’ optical axes. Ill.2, bibl. 5 (in English; abstracts in English, Russian and Lithuanian).